2021
DOI: 10.1021/acs.chemmater.0c04491
|View full text |Cite
|
Sign up to set email alerts
|

Lone-Pair-Induced Structural Ordering in the Mixed-Valent 0D Metal-Halides Rb23BiIIIxSbIII7–xSbV2Cl54 (0 ≤ x ≤ 7)

Abstract: Mixed-valent metal-halides containing n s 2 lone pairs may exhibit intense visible absorption, while zero-dimensional (0D) n s 2 -based metal-chlorides are generally colorless but have demonstrated promising optoelectronic properties suitable for thermometry and radiation detection. Here, we report solvothermally synthesized mixed-valent 0D metal-halides Rb 23 Bi III x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“… 34 Lastly, very recently Benin et al reported a series of mixed valence Sb compounds with formula Rb 23 Bi x Sb 9– x Cl 54 (0 ≤ x ≤ 7), which can be described as Bi doped Rb 2 SbCl 6 , although the structure is significantly more complex than the parent cubic phase. 81 The Bi doping led to lower resistivity than corresponding mixed valence A 2 BX 6 compounds.…”
Section: Discussionmentioning
confidence: 94%
“… 34 Lastly, very recently Benin et al reported a series of mixed valence Sb compounds with formula Rb 23 Bi x Sb 9– x Cl 54 (0 ≤ x ≤ 7), which can be described as Bi doped Rb 2 SbCl 6 , although the structure is significantly more complex than the parent cubic phase. 81 The Bi doping led to lower resistivity than corresponding mixed valence A 2 BX 6 compounds.…”
Section: Discussionmentioning
confidence: 94%
“…Sb-doped OIMHs have been reported to emit blue, orange, or white light, with many applications for near-infrared emission. These findings indicate that appropriate ion doping can break the parity prohibition and induce carrier-absorption transitions, thereby generating colored luminescence. , Noculak et al synthesized Cs 2 MInCl 6 : x Sb (M = Na, K, x = 0–100%) with efficient broadband blue emission (Na, PLQY = 82%) and green emission (K, PLQY = 93%) . Kshirsagar et al reported that Sb 3+ -doped Cs 2 InCl 5 ·H 2 O exhibits highly efficient and strong temperature-dependent green luminescence .…”
Section: Introductionmentioning
confidence: 99%
“…34 Lastly, very recently Benin et al reported a series of mixed valence Sb compounds with formula Rb 23 Bi x Sb 9-x Cl 54 (0 # x # 7), which can be described as Bi doped Rb 2 SbCl 6 , although the structure is signicantly more complex than the parent cubic phase. 81 The Bi doping led to lower resistivity than corresponding mixed valence A 2 BX 6 compounds.…”
Section: Discussionmentioning
confidence: 94%